2023
DOI: 10.55003/cast.2023.06.23.001
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Critical Success Factors of E-Learning Using Structural Equation Model: A Case Study on the Mandatory Use

Abstract: Several researchers have studied e-learning success factors. However, there is rare research linking the success factors from the student perceptions to their data stored in the e-learning system, i.e., the student usage behavior and learning achievement. In addition, there is little research in the literature on mandatory use contexts. Thus, this study aimed to systematically examine and investigate the critical success factors (CSFs) of e-learning used for e-learning evaluation, using an e-learning system i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…[ 61 ] explains that when customers confirm that the purchase lives up to expectations, they would feel satisfied and could cement their loyalty by generating more purchases [ 25 , 32 ]. Several studies have confirmed that learner satisfaction with e-learning can be widely used to assess the success of e-learning [ 5 ]. In this sense [ 62 ], highlights the critical role of satisfaction for the intention of continued use and declares that this has been well established in IS models in marketing and reference disciplines through studies such as those of [ 61 ] or [ 63 ].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 61 ] explains that when customers confirm that the purchase lives up to expectations, they would feel satisfied and could cement their loyalty by generating more purchases [ 25 , 32 ]. Several studies have confirmed that learner satisfaction with e-learning can be widely used to assess the success of e-learning [ 5 ]. In this sense [ 62 ], highlights the critical role of satisfaction for the intention of continued use and declares that this has been well established in IS models in marketing and reference disciplines through studies such as those of [ 61 ] or [ 63 ].…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, e-learning refers to the intervention of technology in the learning process [ 26 ] and although it seems to have become an effective learning medium today [ 4 , 5 ], researchers remain interested in measuring its effectiveness. Something that is not uncommon if we remember that technology is not in itself a panacea for higher education, the changes must be supported by studies on learning outcomes [ 14 , 22 ].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations